2017
DOI: 10.1371/journal.pone.0171227
|View full text |Cite
|
Sign up to set email alerts
|

HIV drug therapy duration; a Swedish real world nationwide cohort study on InfCareHIV 2009-2014

Abstract: BackgroundAs HIV infection needs a lifelong treatment, studying drug therapy duration and factors influencing treatment durability is crucial. The Swedish database InfCareHIV includes high quality data from more than 99% of all patients diagnosed with HIV infection in Sweden and provides a unique opportunity to examine outcomes in a nationwide real world cohort.MethodsAdult patients who started a new therapy defined as a new 3rd agent (all antiretrovirals that are not N[t]RTIs) 2009–2014 with more than 100 obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…No unexpected adverse events were reported and the good tolerability that was seen in previous clinical studies comparing DRV/r with LPV/r or the integrase inhibitors raltegravir and dolutegravir was confirmed [4,6,24]. This is in line with the Swedish InfCare study, where DRV/r was the most commonly used third agent for treatment-experienced patients and showed the lowest risk for treatment discontinuation [22].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…No unexpected adverse events were reported and the good tolerability that was seen in previous clinical studies comparing DRV/r with LPV/r or the integrase inhibitors raltegravir and dolutegravir was confirmed [4,6,24]. This is in line with the Swedish InfCare study, where DRV/r was the most commonly used third agent for treatment-experienced patients and showed the lowest risk for treatment discontinuation [22].…”
Section: Discussionsupporting
confidence: 85%
“…~80% in PROTEA [20] and ~90% in MONET [21]), they only represent half of the patients (48.6%) in this cohort. Similar to the Swedish InfCare study [22], about one-third of the patients were of African ethnicity. More recently published clinical Figure 1.…”
Section: Discussionmentioning
confidence: 57%
“…Using EFV as a reference, the adjusted hazard ratio for discontinuation among treatment-naïve patients was 0.33 for RPV (confidence interval: 0.20-0.54, p < 0.001) and 1.47 for RAL (confidence interval: 1.12-1.92, p = 0.005). Thus, patients on RPV-containing treatments discontinued therapy less often than those on ETR or EFV [113], which is in agreement with the findings of the ECHO/THRIVE trials [47,52].…”
Section: Adherencesupporting
confidence: 87%
“…A study [113] with 2541 patients comparing RPV, ETR, EFV, RAL, lopinavir, ATV, and darunavir found that RPV had the lowest discontinuation rate, while RAL was associated with early discontinuation. After three treatment years, the discontinuation rate among treatment-experienced patients was 22% for RPV, 47% for ETR, and 41% for RAL.…”
Section: Adherencementioning
confidence: 99%
“…Previous analyses of durability have compared people receiving the two NNRTIs without accounting, in the study entry criteria, for the fact that RPV use is restricted to people with an untreated HIV RNA level < 100 000 copies/mL. This makes the interpretation of the comparisons even more difficult [19,20].…”
Section: Introductionmentioning
confidence: 99%